Formation and dynamics of endoplasmic reticulum-like lipid nanotube networks. (7th June 2017) - Bilal, Taylan; Gözen, Irep
Abstract : Phospholipid membranes which are free of curvature-inducing proteins can spontaneously form nanotube networks mimicking the morphology and dynamics of endoplasmic reticulum. Abstract : We report on the self-organized formation and dynamics of artificial lipid nanotube networks, which, in terms of morphology and behavior, resemble the endoplasmic reticulum(ER) of biological cells. The networks, initially generated from a solid-supported planar phospholipid membrane, undergo a morphological transformation, triggered by the chelation and removal of Ca 2+ from the environment surrounding the membrane. Calcium depletion gradually causes de-pinning, thus de-wetting, at the membrane-substrate interface. We observe dynamic re-arrangements very similar to the ones reported for the cellular ER, such as sliding of tubes and formation of new junctions, and quantify these transformations. We also show occurrences of the dynamic replacement of lipidic particles on nanotubes as indicators for the existence of a tension gradient throughout the network, as well as the spontaneous formation of small vesicles from semi-free floating tubes. We propose that these artificial networks are suitable to serve as a bottom-up-generated structural model for the cellular ER, whose fascinating characteristic morphology is suggested to be tied to its biological function, but with respect to formation, dynamics, and functional details still incompletely understood.